Islamic Religious Education Curriculum Based on Islamic Morals: Strategic Steps for Character Education - Mei Cindy Armaini; Juliani; Nazwa Fathiyatul Haq; Amanda Putri Handayani; Nur Fazrah Hasibuan (Journal of Contemporary Islamic Primary Education, 2024)
Education is the most important pillar in building the nation's civilization. Islamic Religious Education (PAI) curriculum based on Islamic morals is an approach in curriculum design and implementation that integrates Islamic teachings, especially in the aspect of morals, as the core of education. The main objective of this curriculum is to educate students not only in the aspect of religious knowledge, but also in the formation of good character in accordance with Islamic moral values. Research methods that can be used to examine the Islamic Education Curriculum based on Islamic morals: strategic step for character education is to use a qualitative method with the type of library study (library research), This library research method is used to analyze where researchers focus more on the use of large numbers of words and language rather than numbers. In addition, in this method, the data collected is data taken from certain sources such as literature, documents, journals, or previous research reports. In shaping the character of students, educators must have strategic ways so that the goals of character education can be achieved optimally, namely: involve all parties, be an example, integrate values and ethics, develop a positive learning environment, Get used to and train, Communicate with respect, Pay attention to child development, Instill disciplinary habits, Tell inspiring experiences, and Plan learning: Lesson planning. In creating character in students, the PAI curriculum must be appropriate, and educators and parents of students must participate more in practicing the moral values that have been taught.